Analisis Bibliometrik pada Augmented Reality dalam Pendidikan: Bagaimana Pemetaannya - Marlina, Marlina; Rahim, Abdul; Awaliyah, Mia; Irhas, Irhas; Patty, Elyakim N.S. (Pendidikan Teknologi Informasi Universitas Bumigora, 2023)
Augmented reality is the latest technology that can connect digital information into a real environment that is used in education. The purpose of this study is to present bibliometric and bibliographical literature on Augmented reality in Education. Bibliometric analysis used VOSviewer which contained 989 literatures from the Google Scholar database published from 2018-2023. The research results show an increase in 2018-2022. In 2023 there will be a decline since there are only a few published articles. There are 9 clusters. Cluster 1 (8 items), cluster 2 (7 items), cluster 3 (6 items), cluster 4 (5 items), cluster 5 (5 items), cluster 6 (3 items), cluster 7 (2 items), cluster 8 (2 items), and cluster 9 (2 items). In addition, papers are published by mostly Indonesian researchers. This study provides information for educational researchers regarding Augmented reality in education in the implementation of learning it seems that not much has been done which is expected to strengthen the topic of further researchers.